Panca Jiwa Pesantren sebagai Modal Sosial untuk Mengatasi Masalah Pengembangan Usaha Ekonomi di Pesantren - Syamsuri Syamsuri; Fuadah Johari; Helmy Fauzy Ahmad; Resi Fauzy Handayani (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
This research aims to analyze how far the internalization of the Pesantren (Islamic Boarding School) values as social capital has become a strategy for solving economic business development problems in Pesantren. One of the main problems Pesantren faces in developing economic businesses is the low quality of human resources and the governance of these economic institutions. The presence of economic businesses within Pesantren holds significant importance. Aside from ensuring the economic sustainability of the institution, it also serves as a platform for nurturing student entrepreneurship, contributing to the overall economic growth of the community. Using the approach of Pesantren values (called Panca Jiwa or Five Principles), namely sincerity, simplicity, independent, Islamic brotherhood (Ukhuwah Islamiyah), and freedom, is expected to be one way to overcome these problems. This research applies the analytic network process, including field surveys, focus group discussions, and in-depth interviews with four groups of respondents: experts, academics, practitioners, and regulators. Respondents were determined by purposive sampling by making Gontor Islamic Boarding School a research location. The results showed that the values of the five principles are internalized into social capital and become solutions to solving problems, like increasing networks with alumni, cooperation between institutions, and so on. This study offers practical implications, namely enabling the resolution of human resource problems with the principle of Islamic brotherhood, and social implications- the success of the economic development of Pesantren can indirectly improve the economic welfare of the surrounding community.